THE IMPACT OF YOUTH URBANIZATION ON THE DEVELOPMENT OF RELIGIOUS LIFE IN THE COMMUNITY - Riyan Syah Afendi; Ilham Mirzaya Putra; Ikhwan Kurnia Hutasuhut (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the impact of Muslim youth urbanization on the development of the community's religious life, as well as the strategies the community uses to face challenges and take advantage of urbanization opportunities in Sidodadi Buluhait Village, South Labuhan Batu. The study uses a qualitative approach with a case study method. There are five research informants: two Muslim youths who have moved to the city, one religious leader, one community leader, and one religious organization administrator. Data was collected through in-depth interviews, observation, and documentation, then analyzed through data condensation, data presentation, and drawing and verifying conclusions using source and technique triangulation. The results show that urbanization has led to reduced direct involvement of youth in religious study sessions, mosque activities, Quranic education, religious organizations, and leadership regeneration processes. However, urbanization also provides opportunities through the experiences, insights, skills, and networks that young people gain in cities. Migrant youth can still contribute through social media, sharing ideas, communication, as well as social and economic support. Communities respond to these conditions by strengthening religious guidance and regeneration, maintaining communication with migrant youth, and making use of digital technology. In this way, Muslim youth urbanization has a double impact: it poses challenges to direct participation and regeneration, while also offering opportunities to strengthen religious life through a more flexible and adaptive form of engagement.